2009
DOI: 10.1007/s11211-009-0105-4
|View full text |Cite
|
Sign up to set email alerts
|

Significant Predictors of Soccer Players’ Moral Functioning from Components of Contextual Injustice, Sensitivity to Injustice and Moral Atmosphere

Abstract: This study analysed the effects of contextual injustice on the moral functioning of soccer players with two goals: (1) to identify the factors of contextual injustice, moral atmosphere and sensitivity to injustice that significantly predict moral functioning and (2) to test the hypothesis that sensitivity to injustice has an effect only in unjust contexts. Three hundred players (from 16 to 40 years old) participated in the study. The analyses indicated a negative and significant effect of contextual injustice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…We examined and found support for this hypothesis in both Study 2 and Study 3 using samples of full-time employees in the work context. Whereas a prior study (Faccenda et al, 2009) using a soccer game scenario reports that those high in victim sensitivity indicate greater levels of intent to retaliate in response to unfairness, our findings are the first we know of to demonstrate this pattern in field settings and when assessing the CWBs of employees.…”
Section: Victim Sensitivitymentioning
confidence: 81%
See 1 more Smart Citation
“…We examined and found support for this hypothesis in both Study 2 and Study 3 using samples of full-time employees in the work context. Whereas a prior study (Faccenda et al, 2009) using a soccer game scenario reports that those high in victim sensitivity indicate greater levels of intent to retaliate in response to unfairness, our findings are the first we know of to demonstrate this pattern in field settings and when assessing the CWBs of employees.…”
Section: Victim Sensitivitymentioning
confidence: 81%
“…In the context of a common goods dilemma, Gollwitzer, Rothmund, Pfeiffer, and Ensenbach () found that those high in victim sensitivity were less likely to cooperate when others had violated rules of fairness. In a scenario study of soccer players, Faccenda, Pantaléon, and Reynes () found that those higher in victim sensitivity reported greater levels of intent to engage in hostile, aggressive behaviors in response to biased referee decisions.…”
Section: Hypothesesmentioning
confidence: 99%
“…Similar results were shown concerning solidarity. In the sports context, Faccenda et al (2009) showed that people sensitive on the victim dimension considered aggressive behaviour to be acceptable, tended to engage more often in such behaviour and confirmed that they would continue to adopt such behaviour. People strongly sensitive on the observer and beneficiary dimensions made the opposite judgements.…”
Section: Sensitivity To Injusticementioning
confidence: 89%
“…Indeed, it has been described as a major variable in explaining transgressions, independently of the context taken into account (school context : Paicheler, 2001;Caillet, 2006; work context: Baron et al, 1999;Ambrose et al, 2002: sports context: Greenberg et al, 1985;Faccenda et al, 2009). In the school context, Caillet (2006) showed that the injustice perceived by students can prompt them to adopt violent behaviour in several situations.…”
Section: Introductionmentioning
confidence: 99%
“…Perpetrator‐sensitive individuals generally score high on other prosocial dimensions of personality, such as tender‐mindedness, modesty, straightforwardness (a moral component of agreeableness), and dutifulness, whereas victim‐sensitive individuals score high on antisocial personality traits such as Machiavellianism, jealousy, and vengeance (Schmitt et al., ; Schmitt et al., ). Broadly speaking, victim sensitivity captures quite self‐oriented justice concerns, including fear of exploitation, suspicion of others' trustworthiness, reduced willingness to cooperate, and antisocial behavioral tendencies (Faccenda, Pantaléon, & Reynes, ; Gollwitzer, Rothmund, Alt, & Jekel, ; Gollwitzer, Rothmund, Pfeiffer, & Ensenbach, ; Gollwitzer et al., ; Rothmund, Gollwitzer, & Klimmt, ). In contrast, perpetrator sensitivity represents other‐related justice concerns.…”
Section: Introductionmentioning
confidence: 99%